Fracture behaviour of concrete with different replacement rates of iron tailings sand based on double-K criterion - Yao Zhang; Wei-Hua Ma; Hong-Zhen Kang; Qiang Li (Fracture and Structural Integrity)
The article conducts a study on the iron tailings sand concrete's fracture behaviour based on the double-K criterion. Five sets of three-point bending beam specimens(100150700)of concrete with 0%, 25%, 50%, 75% and 100% (mass ratio)iron tailings sand replacement river sand respectively were fracture tested, and the P-CMOD and P- e curves of each set of specimens were measured to determine the initial cracking load, unstable cracking load , initial cracking toughness()and unstable cracking toughness(). After the fracture test, samples were extracted from the specimens and subjected to scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP) for microscopic analysis. Macroscopic test results: by comparing the variation pattern of P-CMOD curve and observing the fracture percentage of coarse aggregate in the section, it is found that the fracture processes and damage patterns of iron tailings sand concrete and river sand concrete are comparable; by comparing , , , it is founded that the addition of iron tailings sand improves initial cracking load and initial cracking toughness more significantly than unstable cracking load and unstable cracking toughness; by comparing , and , it is founded that the ductility of iron tailings sand concrete is marginally inferior. Microscopic test results: the SEM images show that the interface transition zone (ITZ) of iron tailings sand concrete is denser and the bonding state is better, and the MIP show that the addition of iron tailings sand can refine the pore size, reduce large pores and increase small pores. Therefore, from the assessment of fracture mechanics, iron tailings sand can totally replace river sand in equivalent quantities for concrete preparation, which will provide great potential for the secondary use of iron tailings sand